Curitiba Walk City: Revitalization of city center by making the city walking friendly, and sustainable - Pissaia de Souza, Henrique; Paulo Mulaski, Pedro (European Journal of Sustainable Development, 2018)
This paper provides an innovative approach to deal with urban problems in the city of Curitiba, Brazil. The paper mixes urban, architecture and economic planning in an applied environmental friendly urban intervention. It proposes a walking system in the city using the already pedestrian walkways implemented in the city with new ones and the construction of pedestrian sky walkways as several implemented around the world, especially in Asia, totaling 7km of walkways in the city center. The project is already in urban scale, showing the feasibility of the project. It is shown that with the project traffic problems will be minimized, safety will be improved; the commercial area will be revitalized and several environmental will be preserved in an economically feasible project. Keywords: walk city, Curitiba, walkways, sky walkways, sustainable development